Developing pro-environmental behaviour: ecotourism fieldtrip and experiences - Ting, D.H. (Emerald Group Publishing Ltd., 2017)
Purpose: This study aims to assess the effectiveness of a student participatory approach and assessment to achieve an environmentally friendly behaviour and change strategy. Design/methodology/approach: Three time-phase studies employed a participatory and experiential case in the form of ecotourism experiential learning and assessment using a sample of 100 higher education students. Findings: The findings suggest that students’ participations through the development, implementation and maintenance of nature-based experiences, combined with professional guides in educating students about sustainable practices has significant and positive effects on pro-environmental behaviour (PEB). The study reveals that social-psychological constructs (except environmental awareness) and socio-demographic variables account for variances in PEB intentions and provides managerial implications for marketers on the use of student participation to enhance behaviour. Practical implications: Experiential and guided learning adds value to PEB through performance accomplishments and instrumental support. Social implications: The guiding principles of moral norms and acting in favour of the community (general social pressure and the underlying normative beliefs) lead to a higher tendency to perform according to the ideal behaviour. Originality/value: This study is the first to use student participation, guided learning, tour guides and experiences to transfer the knowledge of PEB to individuals. © 2017, © Emerald Publishing Limited.